Ultracompact Lens‐Less "Spectrometer in Fiber" Based on Chirped Filament‐Array Gratings. Issue 2 (18th December 2020) - Rahnama, Abdullah; Mahmoud Aghdami, Keivan; Kim, Young Hwan; Herman, Peter R.
Abstract : All‐Fiber Spectrometers In article number 2000026, Abdullah Rahnama and coworkers have harnessed femtosecond laser writing of high aspect ratio filament tracks to form fiber Bragg gratings in single‐mode optical fiber. The filament geometry favored radiative emission into narrow azimuthal zones outside of the cladding by first‐order Bragg diffraction. A chirped filament array enabled lens‐less focusing, to define a compact all‐fiber spectrometer with a moderately high 0.3 nm resolution for light spanning the full visible spectrum.